Compact Broadband Bandstop Filter Based on Composite Right/Left Handed Transmission Line. Issue 4 (19th May 2017) - Song, Kaijun; Zhang, Fan; Fan, Maoyu; Zhu, Yu; Fan, Yong
ABSTRACT: A compact broadband composite right/left handed transmission line (CRLH-TL) bandstop filter based on a triple path signal interference mechanism is presented. The filter incorporates CRLH-TLs, conventional transmission line, and the slotline to implement a compact design. The CRLH-TL is used to realize negative phase shift. The meandered slotline is etched on the ground plane below the interdigital capacitor, which can improve both the in-band and out-of-band performance. The proposed filter avoids the 270/360 degree transmission line in conventional signal interference designs. The equivalent-circuit method is employed to analyze the presented bandstop filter. A broadband bandstop filter centered at 2.45 GHz is designed and fabricated. Good performance is obtained in the stopband as well as in the passband. Calculated, simulated, and measured results show good agreements with each other. The total size of the fabricated bandstop filter is 0.21λ g × 0.11λ g .